Studying the evolution of hypoxia/anoxia in Aitoliko lagoon, Greece, based on measured and modeled data - Knutsen, Øyvind; Stefanakos, Christos; Slagstad, Dag; Ellingsen, Ingrid; Zacharias, Ierotheos; Biliani, Irene; Berg, Arve (Frontiers in Marine Science, 2024)
The present work, which has been carried out in the framework of EEA project BLUE-GREENWAY, is a contribution to the study of the evolution of hypoxia/anoxia in Aitoliko lagoon, Greece. The study area suffers from anoxia which is a very important environmental problem lately mainly due to anthropogenic activities. Unpublished data from two measurement campaigns (2013–2014, 2023) have been used, and a 3D ocean model (SINMOD) has been configured for the region, that couples hydrodynamics, biochemistry and ecology. The analysis of model results includes monthly, annual and interannual variability of fields of dissolved oxygen, temperature, salinity, density, currents and wind as well as Brunt-Väisala frequency and Richardson number. Main results concerning oxygen are: a) the lagoon shows anoxic behavior at 5–7 m depth with a seasonal dependence, b) the seasonal variability in the upper water column with deeper ventilation during winter when the surface stratification is weaker than that during summer, c) anoxic water is reaching the surface of the lagoon for a short period of time.